The impact of Burnout Syndrome on emergency nurses: An integrative review of the literature (Research, Society and Development, 2021)
Objective: To discuss the impact of Burnout Syndrome on emergency nurses. Methodology: This is an integrative review of the literature, following six stages: formation of the hypothesis or inquiry of the research; sampling or search in the literature; data collection; analysis of the studies included in the review; interpretation and discussion of the results; presentation of the integrative review. Results: The 15 articles considered for this study were described in the table, containing identification of the following items: title, author / year, database, methodology and results. The results identified the main signs and symptoms of Burnout that affect the nursing professional, as well as the factors that impact on quality of life, and the characteristics of the emergency department that influence the onset of Burnout syndrome. Conclusion: It is concluded that, the emergency department and a hospital is a place propitious psychosomatic diseases to professionals working in this environment.